Contextualización de los contenidos sobre procesos geomorfológicos en la enseñanza geográfica universitaria: Contextualization of the contents on geomorphological processes in university geography teaching - Labarca Rincón, Ramón; Quintero, Luis Guillermo (Encuentro Educacional, 2024)
The teaching of Geography at the university level must respond to the demands of the contemporary world where geographical phenomena can be seen in situ or through technology. This research aimed to analyze the contextualization of the contents on geomorphological processes in university geography teaching in the Maracaibo municipality of Zulia state. The theoretical foundation was based on Santiago (2021), Labarca (2021), García Ríos (2019), Almoguera (2018), Souto (2018), Pascual Trillo (2017), among others. Methodologically, the study was located in the positivist paradigm and quantitative approach, being a descriptive research with a field design. The information collection was carried out through a Likert-type questionnaire applied to students of education courses taking geographic subjects at the University of Zulia. In the coastal erosion indicator, the results show that the university professor handles the theory, but does not resort to its exemplification in the Zulia coastal landscapes; On the other hand, it is noteworthy that in the wind transport indicator, respondents determined that the example of the Cacique Nigale Cliffs is not used to contextualize the transporting action of the winds. It is concluded that, although the Geography teachers at the university under study have a high level of knowledge of geomorphological processes, there is very little contextualization of such content with the landscapes of Zulia.